Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-762
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Contrast Among Romanian Vowels: Evidence from ASR and Functional Load

Abstract: This work quantifies the phonological contrast between the Romanian central vowels [2] and [1], which are considered separate phonemes, although they are historical allophones with few minimal pairs. We consider the vowels' functional load within the Romanian inventory and the usefulness of the contrast for automatic speech recognition (ASR). Using a 7 hour corpus of automatically aligned broadcast speech, the relative frequencies of vowels are compared across phonological contexts. Results indicate a near com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In Romanian, acoustic analysis of continuous speech has shown that the marginally contrastive /ɨ, ʌ/ distinction is severely diminished, with a phonetic near-merger. The contrast indeed has a very low functional load, and results from automatic speech recognition experiments imply that a merger would have little detrimental impact on word recognition (Renwick, Vasilescu, Dutrey, Lamel, & Vieru, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Romanian, acoustic analysis of continuous speech has shown that the marginally contrastive /ɨ, ʌ/ distinction is severely diminished, with a phonetic near-merger. The contrast indeed has a very low functional load, and results from automatic speech recognition experiments imply that a merger would have little detrimental impact on word recognition (Renwick, Vasilescu, Dutrey, Lamel, & Vieru, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The ASR system described in Vasilescu et al (2014) and Renwick et al (2016) is used in forced alignment mode in this study. Since the manual transcription is provided a priori, the system only has to select the best matching pronunciation for each word, and the corresponding locations of word and phone boundaries.…”
Section: Forced Speech Alignmentmentioning
confidence: 99%
“…The system was used to conduct linguistic investigations based on forced alignment of manual transcriptions with the audio via a lexicon including pronunciation variants. The system allowed for the quantification of the phonemic contrast of Romanian central vowels [2] and [1], through acoustic analysis and the contextual distribution of variants (Renwick et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Two sounds are allophonic if they participate in allophonic alternations conditionedbyaspecificphonemicenvironment,arejudgedtobethesamesoundbynative speakers, and are written with the same grapheme. In addition to work by Hall, other authorshavealsobeguntodefinecontrastusingavarietyofphoneticandusage-based metrics, such as frequency and functional load, see work by Renwick (2014) and Renwick et al (2016). The two most important and often-used criteria in a binary approach are lexical distinction (also called the distinctive function) and predictability of distribution.…”
Section: Criteria For Contrastive Relationshipsmentioning
confidence: 99%